DEVELOPMENT OF COMMUNITY MANAGEMENT OF PUBLIC HEALTH VOLUNTEERS UNDER CORONAVIRUS 2019 IN THE CHAIYA DISTRICT SURAT THANI PROVINCE - Naksong, Tharaphon; Puakkong, Chaiwat; Wangakrangkun, Amorn (Journal of MCU Nakhondhat, 2022)
The purposes of this research were 1) to study community management of health volunteers, 2) to analyze factors affecting community management of health volunteers, and 3) Create guidelines for developing management under the situation of emerging diseases. of public health volunteer personnel in the area of Chaiya District Surat Thani Province using a combined method research model. Data collection with a sample is 400 public health volunteers, Chaiya District, Surat Thani Province, and the main informants were 6 public health officers. Statistics used for data analysis were frequency, percentage, mean, standard deviation. exploratory component analysis and content analysis. The results showed that 1) Community management of health volunteers in general was at a high level ( = 4.12), namely participation ( = 4.21), followed by action. Implementation =4.20), planning ( =4.13), auditing ( =4.08), and improvement ( =3.99), respectively 2) Factors affecting community management of public health volunteers found that there was a campaign for people to wear masks. measure body temperature and always wash their hands with alcohol gel ( = 4.41), followed by knowledge and understanding about self-protection from the coronavirus disease 2019 infection appropriately ( = 4.28), and 3) guidelines. Developing management under the situation of emerging diseases consists of 3 main components, namely 3.1) management skills related to Coronavirus Disease 2019 3.2) knowledge and skills 3.3) leadership in community health problem management by developing a format called MSKTL Model